Infrastructure of Municipal Units - Dmitry N. LEONTIEV; Maxim V. IVANOV; Angelina V. NEVZOROVA (Communications of International Proceedings, 2020)
Due to the significant internal regional diversity of territories, spatial settlement and heterogeneity of the population, Russia is faced with the peculiarities of geographical, natural, demographic, historical characters in the development of modern infrastructure. This explains the timeliness and relevance of the study of modern infrastructure, which is aimed at developing and improving the socio-economic triad towards building its equilibrium model in the field of production, social sphere and housing, as a reflection of the universal infrastructure of the region - an integral part of the country. The study is also aimed at a deep study of theory, facts and a description of various points of view of different authors on this topic. This, in turn, requires the organization of a theoretical attempt to synthesize existing approaches in order to overcome the existing diversity and develop a common view on the essence of the concept of infrastructure. In the process of this study, the experience of summarizing various copyright approaches was considered. At the same time, the authors' points of view and their theoretical justifications became the object of analysis.
Keywords: Regional Infrastructure; Municipalities; Crisis.